Apathy of the Obligation to Provide Public Cemetery Facilities in Residential Areas in West Lombok Regency - Habibi; I Putu Pasek Bagiartha W (IHSA Institute, 2022)
The purpose of this study is to analyze the legal basis for the responsibility for providing funeral facilities in a residential area in West Lombok Regency and the legal force of a housing contract that does not include arrangements regarding rights to public facilities in the form of burial ground . The research used is juridical empirical. The legal basis for regulating the right to a funeral departs from the state's responsibility to provide a proper place to live according to Article 28H Paragraph (1) of the 1945 Constitution and reaffirmed in Law Number 1 of 2011 which is specifically described in Article 9 of the Regulation of the Minister of Home Affairs. Number 9 of 2009. The developer's absence of an obligation to provide a public cemetery area violates the provisions of the sale and purchase contract between the consumer and the housing developer. The cause of the violation of the obligation to provide a burial area by the developer is due to socio-economic considerations and convenience as well as marketing needs, so that it will have an impact on the potential for social conflicts experienced by residents of housing with villagers in the location where the housing is built.